The Influence of Intellectual Capital on LQ45 Companies Performance - Gabriella Alodia Jovita (Jurnal Informatika Ekonomi Bisnis, 2023)
The development of science and technology has led to a shift in businesses from being labor-based to knowledge-based. Companies are expected to create value from the knowledge they possess, which includes their intangible assets. This study aims to examine the relationship between the intellectual capital and the companies’ performance. Some of the previous studies have focused on a tool for measuring intellectual capital called value added intellectual capital (VAIC), which divides intellectual capital into VAHU, STVA, and VACA components. The study population consisted of all LQ45 companies, and a purposive sampling technique was used to select samples. The study used a quantitative approach and employs multiple regression analysis to analyze the data gathered from the financial reports of selected companies. The results indicated that both STVA and VACA have an impact on ROA, while only VACA has impact on TQ. This research creates an awareness among management to properly manage intellectual capital to enhance their overall organizational performance. Further studies may use different measures of intellectual capital and examine organizational performance under.